Structural Regulation of Metal-Organic Frameworks and its Application Prospect in Chrome-Free Tanning - Guanjie HUANG; Jie CHEN; Jianzhong MA (Pige Kexue Yu Gongcheng, 2025)
Metal-organic frameworks (MOFs) are new types of nanomaterials formed by the self-assembly of metal ions and organic ligands, characterized by tunable structure, multiple active sites, and high porosity. Usually, MOFs, prepared through various modification methods such as ligand modification, metal exchange, defect construction and functional loading, can achieve superior physical and chemical properties or unique functionalities, which has attracted widespread attention. The leather industry is one of the important traditional pillar industries of the country, which is closely related to people's lives. Currently, several studies have used MOFs for chrome-free tanning, promoting the green transformation of the leather industry. This article reviewed the synthesis and modification methods of MOFs in recent years. Subsequently, based on the current demand for chrome-free and functional tanning in the leather industry, the application prospects of MOFs as functional chrome-free tanning agents were discussed. This review aims to achieve both the industrial application of MOFs and the green transformation of the leather industry.